2013
DOI: 10.1371/journal.pone.0064395
|View full text |Cite
|
Sign up to set email alerts
|

Low HDL-C Level Is Associated with the Development of Intracranial Artery Stenosis: Analysis from the Chinese IntraCranial AtheroSclerosis (CICAS) Study

Abstract: BackgroundIntracranial atherosclerotic stenosis (ICAS) is an important cause of ischemic stroke worldwide. The role of high-density lipoprotein cholesterol (HDL-C) or low-density lipoprotein cholesterol (LDL-C) in the development of ICAS remains to be elucidated. In the current study, we investigated the relationship of HDL-C level and the risk of developing ICAS in Chinese patients with acute ischemic stroke.MethodsFrom October 2007 to June 2009, a total of 1,984 consecutive ischemic stroke patients were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…3,10 Symptomatic ICASs (50%–99%, Warfarin–Aspirin Symptomatic Intracranial Disease criteria 11 ) in one of the following arterial segments identified on TOF MRA were evaluated in the present study: intracranial portion of internal carotid artery (ICA), M1 segment of middle cerebral artery (MCA-M1), or basilar artery (BA).…”
Section: Methodsmentioning
confidence: 99%
“…3,10 Symptomatic ICASs (50%–99%, Warfarin–Aspirin Symptomatic Intracranial Disease criteria 11 ) in one of the following arterial segments identified on TOF MRA were evaluated in the present study: intracranial portion of internal carotid artery (ICA), M1 segment of middle cerebral artery (MCA-M1), or basilar artery (BA).…”
Section: Methodsmentioning
confidence: 99%
“…Low-density lipoprotein cholesterol (LDL-C) is associated mainly with ECAS [4]. In Chinese populations, high-density lipoprotein-cholesterol (HDL-C) [5], non-high-density lipoprotein-cholesterol (non-HDL-C) [6] and total cholesterol (TC) [7] levels are associated with an increased risk of ICAS. One study based on a Korean population revealed the importance of hypercholesterolemia in ICAS in men [8].…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial atherosclerotic stenosis (ICAS) is associated with 8% to 10% of all ischemic strokes in the United States, but accounts for 33% to 54% of all ischemic strokes in Asia. In China, ICAS may be the cause of 37% to 51% of all strokes or transient ischemic attacks (TIA) [5]. These statistics highlight the importance of understanding the mechanisms involved in the development and elimination of atherosclerotic stenosis.…”
Section: Introductionmentioning
confidence: 99%